Malignant melanoma in HIV: Epidemiology, pathogenesis, and management. Issue 1 (9th December 2019) - Facciolà, Alessio; Venanzi Rullo, Emmanuele; Ceccarelli, Manuela; D'Andrea, Flavia; Coco, Mariagiovanna; Micali, Cristina; Cacopardo, Bruno; Marino, Andrea; Cannavò, Serafinella P.; Di Rosa, Michelino; Condorelli, Fabrizio; Pellicanò, Giovanni F.; et al.
Abstract: People affected by immunodeficiency, and especially those infected by HIV, are burdened by a higher risk of developing malignancies. It has been estimated that the incidence of melanoma in HIV‐infected people is 2.6‐fold higher than in uninfected ones. In this group of patients, melanoma shows a more aggressive phenotype and poorer survival rates compared to HIV‐negative people. Standard guidelines of diagnosis and care do not exist yet. Studies suggest high index of suspicion and a low threshold for biopsy in HIV‐positive patients regardless of their CD4 + count and the use of standard surgical margins for re‐excision procedures. In case of diagnosis of melanoma in HIV‐positive patients, a thorough search for metastatic disease is recommended because of the more aggressive course of this cancer in HIV‐positive patients. Moreover, to rapidly find out any recurrence or metastatic disease after treatment, these patients need a close follow‐up, every 3 months, for the first 2 years and at least twice yearly thereafter. Although surgery remains the main therapeutic option, application of immune checkpoint‐based immunotherapy is being studied and seems to be promising. The aim of this review is to present the current knowledge and future options for melanoma diagnosis and treatment in people living with HIV.